Experimental study of the wake of multi-rotor turbine. (1st February 2023) - Xiong, Xue-Lu; Laima, Shujin; Li, Hui
Abstract: This paper describes a comparative experimental study of the wake of a multi-rotor turbine and a single-rotor turbine. The wake merge process in the multi-rotor wake is analyzed from various perspectives. A jet-like gap flow region and a momentum redistribution region are found in the region before and after the full merge of the individual rotor wakes, respectively. Compared to the single-rotor wake, the fully merged multi-rotor wake is found to have a slower recovery rate and a lower turbulent kinetic energy. Furthermore, two sources are found for the peak frequency in the multi-rotor wake which results in different peak frequencies at different locations. One of the two sources is the rotor wake meandering with the meandering frequency maintain the same throughout the wake, and another one corresponds to the dynamic of the shear layer in the gap region with its peak frequency decrease in the streamwise direction. The yawed multi-rotor wake is found to be similar to the non-yawed case except for the wake deflection of the yawed case. And the deflection is more pronounced in the yawed multi-rotor wake than in the yawed single-rotor wake which indicates a higher yaw efficiency for the multi-rotor turbine. Highlights: A jet-like gap flow is found exists before the full merge of the rotor wakes. A momentum redistribution region exists after the full merge of the rotor wakes. Two sources are found for the peak frequency in the multi-rotor wake. The peak frequency of the shear layer decrease in the streamwise direction. Deflection is more pronounced in the yawed multi-rotor wake than single-rotor case.